(untitled) (Innovaciones Educativas, 2025)
This editorial examines how emotional, distributed, and transformational leadership can serve as a lever for educational quality policies in Latin America. Drawing on evidence linking positive school climates, teacher satisfaction, and student retention with collaborative leadership styles, it argues that organizational well-being should be considered an indicator of quality rather than a side effect. Furthermore, it analyzes findings from international reports and recent research on the presence of distributed leadership and existing gaps. Finally, it proposes an agenda of nine recommendations—ranging from the inclusion of socio-emotional metrics to the strengthening of research networks—aimed at placing well-being and school democracy at the heart of quality policies.